Valuation of 'Villa Igiea' - Kroesbergen, Silvie; Sieber, Patrik, 1977-; Štamfestová, Petra, 1984-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
The aim of this thesis is to provide a detailed analysis for investors willing to invest in ‘Villa Igiea’, located in Palermo, Italy. The thesis is divided in 2 parts: the theoretical part and the practical part. Firstly, the basic valuation principles and different methods of valuation are explained. It is followed up by the explanation of different strategic analysis methods in order to analyze the macro and micro environment of Villa Igiea. The strategic analysis gives a useful base for explaining the income statement and cashflow statement used in the process of calculating the net present value of the hotel.
Vedoucí práce: Patrik Sieber
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses